Writing anthropology : essays on craft and commitment - McGranahan, Carole (Duke University Press, 2020)
"WRITING ANTHROPOLOGY gathers fifty three essays on writing from leading anthropologists on their approach to writing and its current practice in the field. In the past several decades, as anthropologists have grappled with questions of how to ethically portray their subjects, ethnographic writing styles have also changed from a detached, objective voice to one that is more humanistic and self-reflexive. To explore these changes in writing styles and approaches, Carole McGranahan curated a series for the blog Savage Minds: Notes and Queries in Anthropology on the craft of writing and anthropology. This anthology collects expanded versions of these essays, as well as new additions, and raises wide-ranging questions about what it means to write ethnographically. The book is divided into ten sections: Ruminations, Writing Ideas, Telling Stories, On Responsibility, The Urgency of Now, Writing With, Writing Against, Academic Authors, Ethnographic Genres, Becoming and Belonging, and Writing and Knowing. Essays include Ruth Behar on reading as a writer, Adia Benton on how the passage of time can create fuller ethnographic accounts, and Yarimar Bonilla on the temporality of reading and writing in the digital age. Other contributors include Press authors such as Anand Pandian, Lauren Berlant, Kathleen Stewart, Stuart McLean, and Kristen Ghodsee. This book will be of interest to students and scholars of anthropology and creative writing"--
Keywords: Anthropologists' writings; Anthropology : Authorship; antropologia; tieteellinen kirjoittaminen; etnografia; kerronta; fiktio; antropologi; vetenskapligt skrivande; etnografi; berättande; fiktion